A perovskite magnetic nanomaterial and its preparation method and application
Through the preparation of perovskite magnetic nanomaterials, using Co, Ti→Fe doping technology, the problems of high cost and poor renewability of existing adsorbent materials are solved, and efficient adsorption and catalytic degradation are achieved. It is suitable for organic pollutants in water. Removal and regeneration demonstrates strong technical economy.
Patent Information
- Application Number
- CN202211331052.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-10-28
- Publication Date
- 2024-12-31
- Estimated Expiration
- 2042-10-28
AI Technical Summary
Existing adsorbent materials have problems such as high cost, poor renewability, low adsorption capacity and poor adsorption effect in wastewater treatment, and it is difficult to efficiently remove difficult-to-degrade organic pollutants in water.
Prepare perovskite magnetic nanomaterial LaxFe0.55TiyCo0.45-yO3, through dual element doping of Co, Ti→Fe, the adsorption capacity and catalytic activity of the material are enhanced, and efficient adsorption and rapid degradation of organic pollutants are achieved, and magnetic properties are easy to recover. .
This material has high efficiency in removing organic pollutants in water, and can regenerate adsorbents efficiently. It has excellent adsorption capacity and recycling. It is suitable for the treatment of micro pollutants in water and has strong technical and economical properties.
Smart Images

Figure CN115920832B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to a perovskite magnetic nanomaterial and a preparation method and application thereof, and in particular to a perovskite La nanomaterial having both high-efficiency adsorption and catalytic performance in the field of water treatment. x Fe 0.55 Ti y Co 0.45-y O3 magnetic nanomaterials and their preparation methods and applications. Background Art
[0002] Adsorption is one of the most widely used treatment technologies for removing organic pollutants in wastewater treatment. It mainly utilizes the dense pore structure, large specific surface area, high porosity, and surface active groups of the adsorbent material itself to adsorb organic molecules to the surface and pore structure of the adsorbent material through physical or chemical action, thereby achieving the purpose of removing pollutants from water. Currently, the most commonly used adsorbent material is activated carbon material, which has abundant raw materials for preparation, but high preparation cost and poor renewability; while low-cost adsorbent materials such as clay minerals and fly ash, although low-cost, have low adsorption capacity, poor adsorption effect, and narrow application range. The development of low-cost, high adsorption capacity, separable and regenerable adsorbent materials is a key material for energy-saving and water-reduction treatment.
[0003] Chinese invention patent CN111517325A reports a polydopamine-modified carbon material adsorption material. The adsorption material not only has the porous structure of activated carbon, but also is modified by polydopamine, and its surface is rich in imine and phenolic hydroxyl active groups; after modification, the removal efficiency of methylene blue (concentration 20ppm-400ppm) in water is increased from 50.5% to 99.2%. Chinese invention patent CN112121771A reports a biomass adsorption material for removing difficult-to-degrade organic pollutants. The adsorption material uses agricultural waste corn husks as raw materials, acidifies the corn husk powder, loads metal ions on its surface, and has an adsorption capacity of 100mg / g for tetracycline hydrochloride. However, these adsorption materials are used in large quantities, have poor recyclability, and are difficult to recycle. Chinese invention patent CN112588256A reported a magnetic nano bimetallic oxide Fe3O4 / Co3O4 adsorption material, which has a removal efficiency of 92.7% for tetracycline wastewater (concentration 28ppm) after 6 hours. The adsorption material is easy to recycle due to its magnetic properties, but its adsorption rate is slow and the adsorption efficiency is low. The desorption, degradation and removal of adsorbed pollutants still need to be studied and solved. Summary of the invention
[0004] The purpose of the present invention is to provide a perovskite magnetic nanomaterial in order to improve the deficiencies of the prior art. Another purpose of the present invention is to provide a method for preparing the above material. Another purpose of the present invention is to provide the application of the above material in adsorbing organic pollutants in wastewater.
[0005] The idea of the present invention is to prepare high-performance magnetic nano-adsorption materials to improve the removal efficiency of organic pollutants that are difficult to degrade and have trace concentrations in water. The prepared perovskite oxide material composed of transition metals lanthanum, iron, cobalt, and titanium shows excellent adsorption capacity and efficiency for organic pollutants in water (such as dyes, antibiotics, etc.). At the same time, the material has magnetism, which is conducive to the efficient separation and recovery of adsorbents. The catalytic activity of the material can activate the oxidant, quickly degrade the adsorbed pollutants in situ, and realize the efficient regeneration of the adsorbent. As an adsorbent, the magnetic nano-material has outstanding water quality management efficiency and technical economy for the enrichment and removal of micro-pollutants in water.
[0006] The technical solution of the present invention:
[0007] A perovskite magnetic nanomaterial characterized by its molecular structure formula being La x Fe 0.55 Ti y Co 0.45-y O3, belongs to the metal oxide ABO3 configuration, where 0.85≤x≤1, 0.1≤y≤0.4. By doping the lanthanum ferrite matrix material with Co, Ti→Fe, where the molar ratio of lanthanum is 0.85-1, the molar ratio of titanium is 0.1-0.4, and the molar ratio of cobalt is 0.05-0.35, the performance of the material is significantly enhanced. The magnetic nanoparticles prepared by the liquid phase method have the dual functions of high-efficiency adsorption and catalytic activity, and can be used in the treatment of organic micropollutants in the field of water treatment.
[0008] The present invention also provides a method for preparing the above-mentioned perovskite-type magnetic nanomaterial, the specific steps of which are as follows:
[0009] (1) Press La x Fe 0.55 Ti y Co 0.45-y The metal salts containing lanthanum, iron and cobalt and the titanium metal organic compound precursor are weighed in a stoichiometric ratio in the O3 structural formula; the lanthanum metal salt, the iron metal salt and the cobalt metal salt are first dissolved in deionized water, and stirred at room temperature to obtain a mixed metal salt aqueous solution;
[0010] (2) then mixing the titanium metal organic compound precursor and the alcohol aqueous solution in a molar ratio, heating and stirring until the sol is clear and transparent, thereby preparing a titanium dioxide sol;
[0011] (3) adding the prepared titanium dioxide sol dropwise to the mixed metal salt aqueous solution in step (1), adding a complexing agent in a molar ratio, and finally adding a buffer to adjust the pH range, heating and stirring, and evaporating to form a viscous gel;
[0012] (4) After drying the prepared viscous gel, calcining it in an oxygen-containing atmosphere according to a specific temperature increase program, heating it to an intermediate temperature at a certain heating rate and keeping it for a certain time, and then heating it to the target temperature and keeping it for a certain time, finally obtaining a perovskite-type La x Fe 0.55 Ti y Co 0.45-y O3 magnetic material.
[0013] Preferably, the metal salts of lanthanum, iron and cobalt described in step (1) are lanthanum nitrate, iron nitrate and cobalt nitrate, respectively.
[0014] Preferably, in step (2), the titanium metal organic compound precursor is tetrabutyl titanate; the alcohol in the alcohol aqueous solution is a mixture of any one of polymer alcohols and ethanol, and the volume ratio of the polymer alcohol to the ethanol is 1:(3-5); the volume ratio of the alcohol to water in the polymer alcohol aqueous solution is (12-15):1; the molar ratio of the titanium metal organic compound precursor to the alcohol aqueous solution is 3:(13-16); the temperature for heating and stirring the titanium sol is 50°C to 60°C.
[0015] Preferably, the organic complexing agent described in step (3) is a metal salt of citric acid; the buffering agent is ammonia water; the molar ratio of the organic complexing agent to the metal element is (4-5):1; the buffering agent is added to adjust the pH to an acidic range of 3-5; the heating evaporation temperature is 70°C-80°C;.
[0016] Preferably, the temperature for drying the viscous gel in step (4) is 100°C to 120°C; the specific heating program is: the heating rate is 3°C / min to 5°C / min, first heating to 300°C to 400°C and keeping warm for 2 to 3 hours, and then continuing to heat to 700°C to 800°C and keeping warm for 4 to 5 hours.
[0017] The present invention also provides an application of the above-mentioned perovskite-type magnetic nanomaterial in adsorbing organic pollutants in wastewater.
[0018] The present invention prepares a LaO2 perovskite-type molecule based on the compensation mechanism of skeleton metal ions by regulating the key links such as the ratio of transition metal elements in the perovskite-type molecule, the selection of doping elements, and the heating program conditions. x Fe 0.55 Ti y Co 0.45-y O3 perovskite magnetic nanoparticles, this material has excellent adsorption and catalytic degradation properties, high recycling efficiency, and can be used to treat organic micropollutants in water.
[0019] Beneficial effects:
[0020] 1. The magnetic nanoparticles prepared by the present invention have the characteristics of perovskite such as adjustable element ratio, surface charge, oxygen vacancy defects and metal active sites, and exhibit excellent adsorption capacity and efficiency for organic pollutants (such as dyes and antibiotics) in water. The main interactions between nanoparticles and organic molecules include electrostatic attraction, chelation and hydrogen bonding.
[0021] 2. The magnetic nanoparticles prepared by the present invention have catalytic properties, such as activating hydrogen peroxide to generate hydroxyl radicals, so they can degrade organic adsorbents in situ, achieve complete removal of pollutants and efficient regeneration of adsorbents. The magnetic adsorbent has high adsorption performance, strong recyclability, and complete removal of pollutants, making it have outstanding technical and economic benefits in the field of micro-polluted water treatment. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 is a scanning electron microscope image of the perovskite magnetic nanomaterial prepared in Examples 1 to 7;
[0023] Figure 2 1 is a crystal structure X-ray diffraction diagram of the perovskite magnetic nanomaterial prepared in Examples 1 to 7, wherein the left diagram is for Examples 1 to 4, and the right diagram is for Examples 4 to 7;
[0024] Figure 3 It is a magnetization intensity curve diagram of the perovskite magnetic nanomaterials prepared in Examples 1 to 7, wherein the left figure is Examples 1 to 4, and the right figure is Examples 4 to 7;
[0025] Figure 4 It is a graph showing the adsorption performance of methyl blue in water by the perovskite magnetic nanomaterials prepared in Examples 1 to 7, wherein the left graph is for Examples 1 to 4, and the right graph is for Examples 4 to 7;
[0026] Figure 5 It is a graph showing the equilibrium adsorption capacity of the magnetic nanomaterials prepared in Examples 1 to 4 for different concentrations of the dye methyl blue in water;
[0027] Figure 6 It is a graph showing the equilibrium adsorption capacity of the magnetic nanomaterials prepared in Examples 1 to 4 for different concentrations of the antibiotic tetracycline in water;
[0028] Figure 7 This is a graph showing the mass change of the adsorbent of Example 4 prepared as a representative magnetic nanomaterial before and after the adsorption of methyl blue and after regeneration;
[0029] Figure 8 This is a graph showing the test results of five cycles of performance of Example 4 prepared as a representative magnetic nanomaterial in adsorbing methyl blue dye molecules in water. DETAILED DESCRIPTION
[0030] The present invention is further explained in detail below in conjunction with examples. The following examples are limited to illustrating the present invention, but the embodiments of the present invention are not limited thereto.
[0031] Example 1
[0032] La in this embodiment 0.85 Fe 0.55 Ti 0.3 Co 0.15 The preparation method of O3 perovskite material (x=0.85, y=0.3) is as follows:
[0033] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate: cobalt nitrate hexahydrate of 0.85:0.55:0.15, and pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal salt to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:16, wherein the volume ratio of alcohol to water is 15:1 (the volume ratio of ethanol to polyethylene glycol is 3:1), and stir and heat at 60°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 2:1), add sodium citrate (the molar ratio of citric acid to metal element is 5:1), adjust the pH to 4 with an ammonia solution, and continue stirring at 80°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 100°C, then heated from room temperature to 400°C at a rate of 5°C / min in an air atmosphere and kept for 2 h, then continued to be heated to 800°C and kept for 4 h. After natural cooling, the perovskite La 0.85 Fe 0.55 Ti 0.3 Co 0.15 O3 material.
[0034] Example 2
[0035] La in this embodiment 0.90 Fe 0.55 Ti 0.3 Co 0.15 The preparation method of O3 perovskite material (x=0.90, y=0.3) is as follows:
[0036] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate: cobalt nitrate hexahydrate of 0.90:0.55:0.15, and pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal salt to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:16, wherein the volume ratio of alcohol to water is 15:1 (the volume ratio of ethanol to polyethylene glycol is 4:1), and stir and heat at 60°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 2:1), add sodium citrate (the molar ratio of citric acid to metal element is 5:1), adjust the pH to 4 with an ammonia solution, and continue stirring at 80°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 100°C, then heated from room temperature to 400°C at a rate of 5°C / min in an air atmosphere and kept for 2 h, then continued to be heated to 800°C and kept for 4 h. After natural cooling, the perovskite La 0.9 Fe 0.55 Ti 0.3 Co 0.15 O3 material.
[0037] Example 3
[0038] La in this embodiment 0.95 Fe 0.55 Ti 0.3 Co 0.15 The preparation method of O3 perovskite material (x=0.95, y=0.3) is as follows:
[0039] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate: cobalt nitrate hexahydrate of 0.95:0.15:0.55, pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal nitrate to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:13, wherein the volume ratio of alcohol to water is 12:1 (the volume ratio of ethanol to polyethylene glycol is 5:1), and stir and heat at 50°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 2:1), add sodium citrate (the molar ratio of citric acid to metal element is 5:1), adjust the pH to 3 with an ammonia solution, and continue stirring at 70°C until a viscous gel is formed. The obtained wet gel was placed in an oven and dried at 120°C. Then, the temperature was raised from room temperature to 300°C at a rate of 3°C / min in an air atmosphere and kept for 3 h. Then, the temperature was raised to 700°C and kept for 5 h. After natural cooling, the perovskite La 0.95 Fe 0.55 Ti 0.3 Co 0.15 O3 material.
[0040] Example 4
[0041] The LaFe 0.55 Ti 0.3 Co 0.15 The preparation method of O3 perovskite material (x=1, y=0.3) is as follows:
[0042] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate: cobalt nitrate hexahydrate of 1:0.55:0.15, and pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal nitrate to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:13, wherein the volume ratio of alcohol to water is 12:1 (the volume ratio of ethanol to polyethylene glycol is 5:1), and stir and heat at 50°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 2:1), add sodium citrate (the molar ratio of citric acid to metal element is 5:1), adjust the pH to 3 with an ammonia solution, and continue stirring at 70°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 120°C, then heated from room temperature to 300°C at 3°C / min in an air atmosphere and kept warm for 3 h, then continued to rise to 700°C and kept warm for 5 h. After natural cooling, the perovskite LaFe 0.55 Ti 0.3 Co 0.15 O3 material.
[0043] Example 5
[0044] The LaFe 0.55 Ti 0.1 Co 0.35 The preparation method of O3 perovskite material (x=1, y=0.1) includes the following steps:
[0045] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate: cobalt nitrate hexahydrate of 1:0.55:0.35, pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal salt to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:16, wherein the volume ratio of alcohol to water is 15:1 (the volume ratio of ethanol to polyethylene glycol is 4:1), stir and heat to 60°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 2:7), add sodium citrate (the molar ratio of citric acid to metal element is 4:1), adjust the pH to 4 with an ammonia solution, and continue stirring at 80°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 100°C, then heated from room temperature to 400°C at a rate of 5°C / min in an air atmosphere and kept for 2 h, then continued to be heated to 800°C and kept for 4 h. After natural cooling, the perovskite LaFe 0.55 Ti 0.1 Co 0.35 O3 material.
[0046] Example 6
[0047] The LaFe 0.55 Ti 0.2 Co 0.25 The preparation method of O3 perovskite material (x=1, y=0.2) includes the following steps:
[0048] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: cobalt nitrate hexahydrate: iron nitrate nonahydrate of 1:0.25:0.55, pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal salt to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:16, wherein the volume ratio of alcohol to water is 15:1 (the volume ratio of ethanol to polyethylene glycol is 4:1), stir and heat to 60°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 4:5), add sodium citrate (the molar ratio of citric acid to metal element is 4:1), adjust the pH to 4 with an ammonia solution, and continue stirring at 80°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 100°C, then heated from room temperature to 400°C at a rate of 5°C / min in an air atmosphere and kept for 2 h, then continued to be heated to 800°C and kept for 4 h. After natural cooling, the perovskite LaFe 0.55 Ti 0.2 Co 0.25 O3 material.
[0049] Example 7
[0050] The LaFe 0.55 Ti0.4 Co 0.05 The preparation method of O3 perovskite material (x=1, y=0.4) is as follows:
[0051] Weigh the corresponding mass of powder according to the molar ratio of lanthanum nitrate hexahydrate: iron nitrate nonahydrate and cobalt nitrate hexahydrate of 1:0.55:0.05, and pour the weighed powder into the corresponding mass of deionized water to completely dissolve (the molar ratio of metal nitrate to water is 1:1). Mix tetrabutyl titanate and an aqueous solution of alcohol at a molar ratio of 3:13, wherein the volume ratio of alcohol to water is 12:1 (the volume ratio of ethanol to polyethylene glycol is 5:1), and stir and heat at 50°C. Then slowly add the prepared titanium dioxide sol dropwise to the metal nitrate solution (the molar ratio of titanium to cobalt is 8:1), add sodium citrate (the molar ratio of citric acid to metal element is 4:1), adjust the pH to 3 with an ammonia solution, and continue stirring at 70°C until a viscous gel is formed. The obtained wet gel was placed in an oven to dry at 120°C, then heated from room temperature to 300°C at 3°C / min in an air atmosphere and kept warm for 3 h, then continued to rise to 700°C and kept warm for 5 h. After natural cooling, the perovskite LaFe 0.55 Ti 0.4 Co 0.05 O3 material.
[0052] Figure 1 The scanning electron microscope images of the perovskite series magnetic materials prepared in Examples 1 to 7 are shown in the figure. As can be seen from the figure, the average particle size of each series of perovskite type nanoparticles is in the range of 20 to 50 nm, and the agglomeration and accumulation of the nanoparticles form a material with a mesoporous structure.
[0053] Figure 2 The X-ray diffraction patterns of the perovskite series magnetic materials prepared in Examples 1 to 7 are shown in the figure. As shown in the figure, the diffraction planes corresponding to 2θ=22.63°, 32.22°, 39.73°, 46.21°, 52.04°, 57.45°, 67.41°, 72.12° and 76.70° of the reference standard card LaFeO3 (PDF#75-0541) are (100), (110), (111), (200), (210), (211), (220), (221) and (310) crystal planes, respectively. The samples in the examples are consistent with the orthorhombic crystal structure of lanthanum ferrite. At the same time, the doping of metal elements at the B position causes the diffraction peak to shift to the right as a whole.
[0054] Figure 3This is the adsorption curve of the perovskite series magnetic materials prepared in Examples 1 to 7 for the methyl blue dye molecules in water. The adsorption conditions are 0.2 g / L of magnetic adsorbent, 50 mg / L of initial methyl blue concentration, 50 mL of solution volume, and 60 min of ultrasonic mixing. As can be seen from the figure, the methyl blue removal rate quickly reaches 80% to 90% at 10 min; the methyl blue removal rate can reach 98% at 30 min; and the methyl blue removal rate no longer changes significantly at 60 min.
[0055] Figure 4 It is the magnetization intensity curve of the perovskite magnetic material prepared in Examples 1 to 7. As can be seen from the figure, by adjusting the ratio of lanthanum in the A-site metal element lanthanum of lanthanum ferrite, the ferromagnetic behavior of the material does not change significantly; by doping lanthanum ferrite with titanium and cobalt bimetallic elements in the B-site, the ferromagnetic behavior of the material is significantly enhanced.
[0056] Figure 5 The perovskite magnetic material samples of Examples 1 to 4 are graphs of their equilibrium adsorption capacity for different concentrations of methyl blue in water. The adsorption conditions are 0.2 g / L of magnetic adsorbent, 20 mg / L to 1200 mg / L of initial methyl blue concentration, 50 mL of solution volume, and 60 min of ultrasonic mixing. When methyl blue is at a lower concentration (such as 50 mg / L), the adsorption capacity of methyl blue of the samples of Examples 1 to 4 is about 200 mg / g, and the samples of Examples 5 to 7 exhibit similar performance. When methyl blue is at a higher concentration (such as 1200 mg / L), the adsorption capacity of methyl blue of the samples of Examples 1 to 4 is in the range of 1500 mg / g to 2000 mg / g, and the samples of Examples 5 to 7 exhibit similar performance. Among them, the equilibrium adsorption capacity of methyl blue of Example 4 can reach up to 2313 mg / g.
[0057] Figure 6 The perovskite magnetic material samples of Examples 1 to 4 are graphs of their equilibrium adsorption capacity for different concentrations of tetracycline in water. The adsorption conditions are 0.2 g / L of magnetic adsorbent, 5 mg / L to 100 mg / L of initial tetracycline concentration, 50 mL of solution volume, and 60 min of ultrasonic mixing. When tetracycline is at a lower concentration (such as 50 mg / L), the adsorption capacity of tetracycline for samples of Examples 1 to 4 is in the range of 50 mg / g to 100 mg / g, and samples of Examples 5 to 7 exhibit similar performance. When tetracycline is at a higher concentration (such as 200 mg / L), the adsorption capacity of methyl blue for samples of Examples 1 to 4 is in the range of 200 mg / g to 300 mg / g, and samples of Examples 5 to 7 exhibit similar performance. Among them, the equilibrium adsorption capacity of tetracycline in Example 4 can reach up to 263 mg / g.
[0058] Figure 7Example 4 is used as a representative sample to show the mass change of the adsorbent before and after adsorption. The adsorption conditions are 0.2 g / L magnetic adsorbent, 50 mg / L initial methyl blue concentration, 50 mL solution volume, and 60 min ultrasonic mixing. As can be seen from the figure, the mass of the fresh adsorbent is 10 mg; the mass increases to 32 mg after adsorption; and the mass recovers to 13 mg after regeneration of the adsorbent. The material can be effectively regenerated by chemical cleaning.
[0059] Figure 8 The results of five cycles of adsorption of methylene blue in water by Example 4 as a representative sample are shown in Figure 4. The adsorption conditions are 0.2 g / L magnetic adsorbent, 50 mg / L initial concentration of methylene blue, 50 mL solution volume, 50 mL solution volume, and 60 min ultrasonic mixing. As can be seen from the figure, from the first adsorption test to the fifth test, the equilibrium adsorption capacity (q e ) were 233mg / g, 222mg / g, 213mg / g, 210mg / g and 201mg / g respectively. After five cycles of use, the recovery rate of the adsorption performance of the magnetic material reached 86%.
[0060] From the above results, it can be seen that the perovskite magnetic nanomaterial prepared by the present invention can be used for the efficient enrichment and removal of difficult-to-degrade organic pollutants (such as dyes and antibiotics) in water. The material not only has excellent adsorption efficiency and capacity, but also has the performance of efficient separation, regeneration and recycling, and has strong technical and economic efficiency. Therefore, the application prospect of adsorption technology in the field of wastewater treatment is broad.
Claims
1. A perovskite-type magnetic nanomaterial, characterized in that The molecular structure is La x Fe 0.55 Ti y Co 0.45-y O3 belongs to the metal oxide ABO3 configuration, where 0.85≤x≤1, 0.1≤y≤0.
4. The material has both high adsorption and catalytic functions.
2. A method for preparing the perovskite-type magnetic nanomaterial as claimed in claim 1, wherein the specific steps are as follows: (1) Press La x Fe 0.55 Ti y Co 0.45-y The metal salts containing lanthanum, iron and cobalt and the titanium metal organic compound precursor are weighed in a stoichiometric ratio in the O3 structural formula; the lanthanum metal salt, the iron metal salt and the cobalt metal salt are first dissolved in deionized water and stirred to obtain a mixed metal salt aqueous solution; (2) then mixing the titanium metal organic compound precursor and the alcohol aqueous solution in a molar ratio, heating and stirring until the sol is clear and transparent, thereby preparing a titanium dioxide sol; (3) adding the prepared titanium dioxide sol dropwise to the mixed metal salt aqueous solution in step (1), adding a complexing agent in a molar ratio, and finally adding a buffer to adjust the pH range, heating and stirring, and evaporating to form a viscous gel; (4) drying the prepared viscous gel, and then calcining it in an oxygen-containing atmosphere according to a specific temperature increase program. Finally, the perovskite La x Fe 0.55 Ti y Co 0.45-y O3 magnetic material; wherein the specific heating program is: the heating rate is 3℃ / min~5℃ / min, first heated to 300℃~400℃ and kept warm for 2~3 hours, Then continue to heat to 700℃~800℃ and keep warm for 4~5 hours.
3. The method according to claim 2, characterized in that: The metal salts of lanthanum, iron and cobalt described in step (1) are lanthanum nitrate, iron nitrate and cobalt nitrate respectively.
4. The method according to claim 2, characterized in that: In the step (2), the titanium metal organic compound precursor is tetrabutyl titanate; the alcohol in the alcohol aqueous solution is a mixture of any one of polymer alcohols and ethanol, and the volume ratio of the polymer alcohol to ethanol is 1:(3-5); the volume ratio of alcohol to water in the alcohol aqueous solution is (12-15):1; the molar ratio of the titanium metal organic compound precursor to the alcohol aqueous solution is 3:(13-16); the temperature for heating and stirring the titanium dioxide sol is 50°C to 60°C.
5. The method according to claim 2, characterized in that: The complexing agent in step (3) is a metal salt of citric acid; the buffer is ammonia water; the molar ratio of the organic complexing agent to the metal element is (4-5):1; the buffer is added to adjust the pH to an acidic range of 3-5; and the heating evaporation temperature is 70°C-80°C.
6. The method according to claim 2, characterized in that: The temperature for drying the viscous gel in step (4) is 100°C to 120°C.
7. Use of the perovskite-type magnetic nanomaterial as claimed in claim 1 in adsorbing organic pollutants in wastewater.
